Pengaruh Senam Otak terhadap Kesehatan Mental Lanjut Usia - Farahdina Bachtiar (Jurnal Fisioterapi dan Rehabilitasi, 2019)
Introduction: An increase in the elderly population is something that cannot be avoided as an effect of improving people's quality of life. However, this is a challenge because many elderly not only experience physical disorders but also mental disorders. Various studies have found that physical activity can improve mental health in the elderly. Therefore, this study aims to examine the effect of brain gym exercise on mental health of the elderly. Methods: This study used an experimental research design. The sample used was elderly women who visited Puskesmas Tamalanrea Jaya Makassar. The number of samples in this study was 20 elderly people divided into the treatment group and control group. The treatment group received the elderly gym and brain gym while the control group was only given elderly gym. Mental status for all elderly people was measured using the Beck Depression Inventory (BDI) II questionnaire. The data obtained were analyzed using the SPSS 22.0 for Windows package. Results: The results showed that there were significant changes in mental status after brain gym exercise in the treatment group (p<0.05), whereas there were no significant changes in mental status after elderly gym exercise in the control group (p>0.05). In addition, it was found that there were no significant differences in the value of mental status between the treatment group and the control group (p> 0.05). However, the mean value of mental status in the treatment group was greater than the mean value in the control group. Conclusion: Therefore, it can be concluded that there is an effect of brain gym exercise to changes in mental status in the elderly. Mental status in the treatment group after administration of brain gym was better compared to the control group.